Kejawaan Dan Keislaman: Satu Pertarungan Identitas - Sugeng Bayu Wahyono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
The resurgence of political Islam has widened the space for expressing Islamic identity. Along with such a resurgence struggle for revitalize Javanese-ism which in turn provide a sound basis for regaining Javanese identity. The relationship between Javanese-ism and Islamism is best understood in term of the sought of collective identity, instead of syncretism.